2019
DOI: 10.1111/acer.14146
|View full text |Cite
|
Sign up to set email alerts
|

Different Effects of Knockouts in ALDH2 and ACSS2 on Embryonic Stem Cell Differentiation

Abstract: Background: Ethanol (EtOH) is a teratogen that causes severe birth defects, but the mechanisms by which EtOH affects stem cell differentiation are unclear. Our goal here is to examine the effects of EtOH and its metabolites, acetaldehyde (AcH) and acetate, on embryonic stem cell (ESC) differentiation.Methods: We designed ESC lines in which aldehyde dehydrogenase (ALDH2, NCBI#11669) and acyl-CoA synthetase short-chain family member 2 (ACSS2, NCBI#60525) were knocked out by CRISPR-Cas9 technology. We selected th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 63 publications
(99 reference statements)
0
15
0
Order By: Relevance
“…This procedure was repeated in six wells. Three time points (24,48, and 72 hr) were set for the subsequent experiments. Each well was added with 20 μL cell counting kit-8 (CCK-8) solution (5 mg/mL), which was incubated at 37 C for 2 hr, and then the culture was terminated.…”
Section: Cell Counting Kit-8 Assaymentioning
confidence: 99%
See 3 more Smart Citations
“…This procedure was repeated in six wells. Three time points (24,48, and 72 hr) were set for the subsequent experiments. Each well was added with 20 μL cell counting kit-8 (CCK-8) solution (5 mg/mL), which was incubated at 37 C for 2 hr, and then the culture was terminated.…”
Section: Cell Counting Kit-8 Assaymentioning
confidence: 99%
“…Evidence has shown that inhibition of ALDH can significantly reduce the stemness characteristics of stem cells. 24 To investigate whether FOXM1 affects the stemness characteristics of LCSCs by regulating ALDH2, we tested the expression of ALDH2 protein after silencing FOXM1 by western blot analysis.…”
Section: Silencing Foxm1 Suppresses the Stemness Of Lcscs By Decreasing The Expression Of Aldh2mentioning
confidence: 99%
See 2 more Smart Citations
“…Our lab has shown that AcH is preferentially metabolized by ALDH2, and not ALDH1A2, using ESC knockout cell lines for each gene and measuring the formation of NADH from NAD + in lysates [69]. ALDH2-null ESCs display lower transcript levels of several pluripotency markers (Nanog, Sox2, Klf4) than WT ESCs [69]. The responses of ALDH2-KO ESCs to EtOH are complex.…”
Section: Knockout and Overexpression Models Using Stem Cellsmentioning
confidence: 99%